Religion and horror : how the American religious press viewed the death camps and Holocaust survivors - Camp, William D. 1981- (Xulon Press, 2019)
This study probes the American religious press between 1943 and 1945 to determine what was reported about Nazi death camps. Catholic and Protestant periodicals between 1945 and 1949 are also examined to evaluate the impact that the Holocaust had on the creation of a Jewish state in Palestine. How much did American Catholics and Protestants know about Nazi persecution of Jews? When did the American Christian press begin to report on the existence of death camps? If Protestant and Catholic periodicals described the killing of Jews by the Nazis, was any pressure put on the United States government to stop the murders (bomb rail lines leading to Auschwitz)? Did the religious press portray problems of survivors of the Holocaust? Did the press carry any editorials or articles in support of a Jewish homeland in Palestine for Holocaust refugees? --